New trends in teaching German as a foreign language and their consequences for designing new handbooks - Ciepielewska-Kaczmarek, Luiza (Glottodidactica, 2010)
The following factors have contributed to arising new target groups in teaching foreign languages: the European Union’s claim concerning the multilingualism of its members, migrations, common mobility. As a consequence of this situation new handbooks for teaching and learning foreign languages have appeared on the market. Thus, the teacher is often confronted with the necessity of choosing the handbook, which is most adequate for the needs of a particular group of learners. The present article aims at defining the criteria of handbook selection in the light of the latest trends in foreign language teaching methodology.